Hybrid Organic-Inorganic Mononuclear Lanthanoid Single Ion Magnets - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P; Canon-Mancisidor, W; Canon-Mancisidor, W; Zapata-Lizama, M; Zapata-Lizama, M (Royal Society of Chemistry, 2019)
The first family of hybrid mononuclear organic-inorganic lanthanoid complexes is reported, based on [PW11O39]7- and 1,10-phenanthroline ligands. This hybrid approach causes a dramatic improvement of the relaxation time (×1000) with a decrease of the optimal field while maintaining the Ueff of the inorganic analogues. This journal is © The Royal Society of Chemistry.